KARAKTERISASI BAHAN FEROELEKTRIK BARIUM STRONTIUM TITANAT (Ba0,7 Sr0,3TiO3) MENGGUNAKAN MIKROSKOP IMBASAN ELEKTRON (SEM) - Rizki, Befriana Ayu; Dewi, Rahmi; ', Sugianto (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Ferroelectric  of Ba0,7Sr0,3TiO3  has been made  from  BaCO3  (Barium Carbonat), SrCO3(Strontium Carbonat),  and TiO2  (Titanat Oksida)  with variation  of  calcination temperatures  of  600oC, 700oC,  and 800oC.  Ferroelectric product  of Ba0,7Sr0,3TiO3  was characterized by Scanning Electron Microscopy (SEM). Sizes  of ferroelectric particle increased  with  sintering  temperatures,  as follow  1,67µm, 2,27µm,  and 2,38µm for samples with high temperature  of  600oC, 700oC and 800oC. Respectively then  the density of particle decreased with  temperature i.e 5,03x10-4 %, 4,40x10-4 %, and 1,52x10-4 %.  The average value of resistance increased  with  calcination  temperature  and sintering  temperature of 400oC, 600oC, 700oC and 800°C  i.e  6,716x108Ω, 6,740x108 Ω, 6,754x10 8 Ω and 6,768x108 Ω, as well as the value of the average resistivity increased with  rise  in calcination  temperature  and sintering temperature  as follow 193,122x108 Ωm, 194,884x108 Ωm, 196,784x108 Ωm,  and 198,882x108Ωm. These  were due to the effect of temperature on the arrangement  of the material  atoms.  It was concluded then the resistivity of a material does not depend on its geometric shape but depend on the temperature of the material.